Imagining Babylon : The Modern Story of the Ancient City - Liverani, Mario (Studies in Ancient near Eastern Records (SANER) Ser, 2016)
Intro -- Preface to the Italian Edition -- Contents -- List of figures -- Abbreviations -- Journals -- Series -- 1 Rediscovery and perplexity -- 1.1 The ruins and the biblical curse -- 1.2 Imagining unknown cities -- 1.3 The rediscovery of the Assyrian capitals -- 1.4 The techniques of excavation and the problems of visibility -- 1.5 Ancient cities and eastern cities -- the material, and the values -- 1.6 Ideology and town planning: a city and not a city -- 1.7 From the Assyrians to the Sumerians -- 1.8 Stripping the tell -- 2 Acceptance and modification -- 2.1 The 'discovery of bricks' and the architectural revolution -- 2.2 From Liberty to Bauhaus: the city takes form -- 2.3 The ancient descriptions -- 2.4 Imagining Jerusalem -- 2.5 Above the flood plain: Anatolia and Iran -- 2.6 The Near-Eastern village and its eclipse -- 2.7 Evolutionism and economic history -- 2.8 Max Weber: the separate ways -- 2.9 Anna Schneider and the Sumerian temple-city -- 2.10 New procedures: the inventory of the country -- 2.11 New procedures: excavation by squares -- 2.12 The 'colonial' excavations: palaces and urban neighbourhoods -- 2.13 Henri Frankfort, from Egypt to the Diyala -- 3 The season of theoretical models -- 3.1 Gordon Childe: the urban revolution and evolutionary heritage -- 3.2 Thorkild Jacobsen and 'primitive democracy' -- 3.3 Igor Diakonoff, the 'Asiatic mode' and the residual village -- 3.4 Karl Wittfogel and the 'hydraulic' city -- 3.5 Karl Polanyi and the redistributive city -- 3.6 The Chicago school: 'City Invincible' and the young Adams -- 3.7 The wider scenes: Mumford, Sjoberg, Jacobs -- 3.8 Neo-evolutionism: city and archaic state -- 3.9 After Babylon: Greek urbanization and the Islamic city -- 4 The new models in practice -- 4.1 Robert Braidwood, the Jarmo project and the arrival of the palaeo-sciences.